Implementation of the social assistance program for people with severe disabilities: A disability and social inclusion perspective - Daulay, Lia Apriolita (Journal of Gender Equality Disability Social Inclusion and Children, 2025)
Background: The assumption that disability is a disgrace, curse and shame makes families not open about their family members who have disabilities. In addition, the assessment of society that considers people with disabilities to be unproductive and unable to carry out tasks and responsibilities because of their physical disabilities. Often people with disabilities are equated with sick people, helpless, so they do not need to be given education and work, just pitied and cared for for their survival. Methods: This research approach is a qualitative approach, namely by reviewing data that begins with reviewing all available data from various data sources that have been collected, studying data, reviewing, compiling it into a unit. Findings: People with disabilities face both physical and mental limitations, compounded by a lack of support from their families and communities. This isolation leads to feelings of inferiority, social difficulties, and limited participation in life’s activities. Their social roles are often hindered, resulting in further marginalization. Conclusion: Based on data from the results of the research conducted, the Implementation of the Social Assistance Program for People with Severe Disabilities (ASPDB) in Harjosari II Village has not been running well. Of the four variables of George C. Edward III's Implementation Theory, only variable (3) disposition has been running well. While variables (1) communication (2) resources and (4) bureaucratic structure have not been running well. Novelty/Originality of this Study: This study offers a unique perspective on the challenges in implementing the Social Assistance Program for People with Severe Disabilities/Asistensi Sosial Penyandang Disabilitas Berat (ASPDB) in Harjosari II Village, using George C. Edward III's Implementation Theory. It highlights issues in communication, resources, and bureaucratic structure, contributing valuable insights for improving disability support programs.